Proton currents in human granulocytes: regulation by membrane potential and intracellular pH. - Demaurex, N (1993)
1. To determine whether conductive pathways contribute to the H+ efflux from granulocytes, we used the whole-cell patch-clamp technique combined with microfluorimetric determinations of cytosolic pH (pHi) in single, dimethylsulphoxide-differentiated HL-60 cells. 2. In voltage-clamp mode, depolarization of the cell from the resting potential (around -60 mV) to +60 mV caused an increase in pHi that was accompanied by a sizeable outward current. 3. Ion substitution experiments and analysis of the reversal potential of tail currents indicated that the outward current is carried largely by H+ ions. 4. Full activation of the H+ current occurred within 1-2s after depolarization and deactivation within 100-200 ms upon repolarization. 5. This H+ conductance was strongly dependent on pHi, being larger at acidic pH. In addition, at low pHi the threshold for voltage activation of the H+ conductance was shifted to more negative values. 6. Addition of millimolar concentrations of Cd2+ and Zn2+ to the bath solution reduced the maximum H+ conductance and shifted the voltage dependence of the H+ conductance to more positive potentials. The effects were reversible. 7. In conclusion, our results demonstrate that granulocytic HL-60 cells possess a voltage-gated and pHi-sensitive H+ conductance. Because both a depolarization and a cytosolic acidification occur during the activation of granulocytes, this conductance may play a role in pHi homeostasis of granulocytes during microbial killing.